First characterisation of minor and neglected Vitis vinifera L. cultivars from Mount Etna - Filippo Ferlito; Elisabetta Nicolosi; Stefano La Malfa; Antonio Cicala; Alessandra Gentile (Horticultural Science, 2018)
Eight minor and neglected cultivars of Vitis vinifera L. were characterised according to their ampelographic and agronomic traits and discriminated by molecular analysis with SSR markers. These results are the first complete ampelographic description of these minor and neglected cultivars from the Mount Etna region. The results of this study reveal high morphological diversity of ancient grapevines growing in this region. SSR markers enabled us to discriminate the cultivars and revealed the genetic divergence between them and several autochthonous cultivars. Our efforts could contribute to a better knowledge of grape biodiversity based on morphological and molecular data and could be useful for the development of a reliable germplasm conservation strategy.